Report of the Team for the Study of Community Projects and National Extension Service Vol. 1 - Planning Commission (Planning Commission, Government of India, 1957)
The 1957 Report on Community Projects and the National Extension Service presents a comprehensive evaluation of India’s rural development strategy within the framework of the Second Five-Year Plan, emphasizing efficiency, administrative economy, and grassroots participation. Conceived to review the content, coordination, personnel structure, financing, and evaluative mechanisms of community development initiatives, the report underscores the evolution of community development from a narrow rural upliftment concept to a broader socio-economic transformation rooted in democratic decentralization. It advocates empowering statutory local bodies such as Panchayat Samitis, strengthening the role of Block Development Officers, and improving coordination among district collectors and departmental heads to reduce fragmentation and enhance accountability. Financial inadequacies, personnel shortages, and insufficient training are identified as major constraints, prompting recommendations for expanded training infrastructure, clearer administrative hierarchies, and continuous evaluation systems. Sectoral analyses highlight the need for improved agricultural practices, irrigation expansion, soil conservation, animal husbandry, poultry and fisheries development, revitalization of the cooperative movement with inclusive credit access, and integration of rural industries to enhance employment. The report further stresses coordinated welfare strategies for women and children, strengthened public health systems through departmental integration, improved sanitation and drinking water facilities, expanded educational outreach including adult literacy, and culturally sensitive development models in tribal areas. Emphasizing both local financial contributions and self-reliant maintenance of assets, the document calls for a balanced synthesis of top-down planning and bottom-up participation. Ultimately, it envisions a decentralized, well-coordinated, and community-driven development framework capable of fostering sustainable rural transformation and achieving the broader socio-economic goals of national planning.
Committee on Plan Projects New Delhi November 1957
Keywords: Community Projects; National Extension Service; Democratic Decentralization; Panchayat Samiti; Block Development Officer; Agricultural Development; Cooperative Movement; Rural Industries; Women and Child Welfare; Public Health Integration; Irrigation Expansion; Capacity Building